Prevalence, Risk Factors, and Perinatal Outcomes of Anemia Among Pregnant Women - Mathew, Preethi; More, Sakshi; Khaire, Charushila; Totare, Anjali; Dhindale, Kirti; Marian, Christina; Gavandi, Juned (International Journal of Nursing Research, 2024)
Introduction: Anemia is a crucial common health problem affecting the developed as well as the developing world. Around the world, malnutrition is the most common cause for child and maternal death. The aim of the study is to determine the prevalence and outcome of anemia in pregnancy and her new. Methodology: Quantitative approach with descriptive survey method was used. Data were collected from 107 pregnant women using the non-probability purposive sampling technique. Result: The majority 103 (96.2%) of pregnant women are belong to the age of 20–30 years and mostly 62 (57.9%) were Hindu. The mode of delivery of pregnant anemic women shows that the majority 21 (70%) of women delivered vaginally. The majority of the mothers, 103 (96.3%), did not have a previous history of abortion. The distribution of weight of the newborn at birth states that the majority of newborns weighed above 2.5 kg (69%). The distribution of pregnant mothers based on associated risk factors reveals that only 5 (4.7%) pregnant women had thyroid problems, gestational DM, and epilepsy one each. The prevalence of anemia based on severity showed that most of the mothers 85 (78.4%) had moderate anemia as per the WHO classification. Conclusion: The study concludes that moderate anemia is prevalent among pregnant women. Some of the health problems associated with anemia are thyroid problems, gestational DM, and epilepsy.